ABRAHAM MASLOW HUMANISTIC APPROACH THROUGH COOPERATIVE LEARNING ON SOCIAL STUDIES SUBJECTS - Irfan; Lusi Oktavia; Mei Akbar Velayati; S. Nudia Mastur; Astri (Auladuna: Jurnal Pendidikan Dasar Islam, 2023)
Abstract This research was conducted to identify the humanistic approach of Abraham Maslow's theory in cooperative learning in social studies subjects in class V by focusing on Abraham Maslow's 5 needs regarding the achievement of each need. The method used was qualitative method with descriptive analysis. Data were obtained through interviews, observation, and documents. The results of this research indicated that physiological needs, social needs, needs to be appreciated, and self-actualization needs have not been properly actualized, this is because: (1) teachers were still lacking in the mastery of cooperative learning techniques, (2) the atmosphere was unconducive, and the students were less compact in completing assignments, (3) students had not yet developed a sense of appreciation, so they still needed teacher instruction, and (4) some students could not express the material studied in class. The need for a sense of security had been implemented properly because the teacher gave the freedom to ask, answer, and accept the opinions expressed by his/her students.